2018
DOI: 10.17533/udea.iee.v36n1e01
|View full text |Cite
|
Sign up to set email alerts
|

Promotion and Enhancement of Knowledge in Nursing

Abstract: Knowledge is the product of the action of learning and has as requisite that it can be expressed and communicated to others. (1) According to Fawcett, (2) one of the central issues for the survival of nursing as a discipline is understanding the nature and structure of nursing knowledge. This can be interpreted as the clarity about that which should be investigated, what should be done in the practice, and what should be taught during the formation of professionals. Although research, practice, and formation h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 11 publications
0
3
0
6
Order By: Relevance
“…Clinical skills represent an important component in nursing practice, and nursing knowledge, which is associated with proficiency, is fundamental in guiding logical reasoning and decision‐making to deliver safe care to patients (Dilles et al, 2011; Osorio‐Castaño, 2018). It has been shown that the risk of medication errors is higher among nurses with poorer nursing knowledge (Simonsen et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Clinical skills represent an important component in nursing practice, and nursing knowledge, which is associated with proficiency, is fundamental in guiding logical reasoning and decision‐making to deliver safe care to patients (Dilles et al, 2011; Osorio‐Castaño, 2018). It has been shown that the risk of medication errors is higher among nurses with poorer nursing knowledge (Simonsen et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…5 The Nursing profession aims to produce knowledgeable, competent, and autonomous nurses that can provide quality care in any situationirrespective of physical setting whether it behospital, community, or home. 6 Moreover, an effective clinical practice necessitates the application of understanding, skills, critical thinking, and art of care in aproficient, ef-fective, and thoughtful method. 7 This can be attained through acombination of knowledge, practice, and theories in nursing.…”
Section: Introductionmentioning
confidence: 99%
“…2 La Enfermería por su parte, toma alguna de estas para llevar a cabo la formación de su propio saber, las cuales actualmente conocemos como estructura del conocimiento. 3…”
unclassified
“…La Enfermería ha tenido un giro bastante amplio en su desarrollo científico y disciplinar en los últimos años, centrándose en el cuidado de la persona; por lo tanto, basa su saber en el ser humano. 3,4 Las personas están en constante transformación, esto hace que la profesión de Enfermería sea una disciplina dinámica, variando entre culturas en cuanto a su expresión, procesos y patrones. 4 Si bien la formación del saber depende de cada disciplina, este tiene que ser generado, comprobado y empleado, por lo tanto, la Enfermería se encuentra en una búsqueda incesante de la creación de un propio marco en el cual fundamentar la identidad de la disciplina.…”
unclassified
See 1 more Smart Citation